Design of constant force polishing device for castings based on kinematic analysis - Zhao, Feifei (Frontiers in Mechanical Engineering, 2026)
IntroductionIn response to the problem of insufficient stability in force control of existing polishing equipment, this study aims to develop a casting constant force polishing device based on kinematic analysis to meet the high-precision and high-efficiency requirements of surface machining of large castings.MethodsStarting from the casting processing technology, combined with mechanical principles and optimization design methods, the overall structural design and optimization of the polishing device are completed. At the same time, a kinematic model is established and a control system based on programmable logic controller is constructed.ResultsThe results of motion simulation and adaptability verification show that the polishing device exhibits good adaptability and stability under different surface characteristics of castings, and the trajectory accuracy can reach up to 90%. The average polishing force can quickly stabilize under different characteristics, and the average polishing force of planar features remains stable between 490 N and 500 N with minimal fluctuations. The improved proportional-integral-derivative control strategy significantly improves control accuracy and response speed, with a minimum root mean square error value of 0.08 and an error recovery time of only 4.0 s.DiscussionThe research designed constant force polishing device for castings not only improves the surface machining quality of castings, but also provides an efficient and stable solution for automated polishing of large castings, which has important industrial application value.